2000
DOI: 10.1046/j.1365-2044.2000.01535.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of peribulbar bupivacaine as an adjunct to general anaesthesia on peri‐operative outcome following retinal detachment surgery

Abstract: SummarySixty premedicated, ASA physical status I or II patients weighing . 25 kg scheduled for elective retinal detachment repair were randomly assigned to receive either peribulbar block with 10 ml of 0.25% bupivacaine (block group) or intravenous morphine 150 mg.kg 21 (morphine group), prior to the induction of general anaesthesia (n 30 in each group). Patients were evaluated for intraoperative oculocardiac reflex , peri-operative pain relief, recovery from anaesthesia and postoperative nausea and vomiting. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
45
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 26 publications
5
45
2
Order By: Relevance
“…However, although results of that study 26 indicated 4 mL was appropriate for PBA, a volume of 3 mL was used in the present study because of 2 concerns: ensuring we did not exceed a bupivacaine dose of 2 mg/kg to avoid systemic toxicosis, [35][36][37][38][39][40][41] and maintaining a bupivacaine concentration > 0.25% because lower concentrations of the anesthetic may lead to decreased efficacy. 4,42,43 Given that distribution of the injectate around the optic nerve was only 90° to 180° in 3 of 6 PBA-treated eyes, it is possible that a larger volume (4 mL) was indicated for PBA. Addition of the contrast agent in the present study also may have affected distribution of the bupivacaine, but it was essential for the CT monitoring.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, although results of that study 26 indicated 4 mL was appropriate for PBA, a volume of 3 mL was used in the present study because of 2 concerns: ensuring we did not exceed a bupivacaine dose of 2 mg/kg to avoid systemic toxicosis, [35][36][37][38][39][40][41] and maintaining a bupivacaine concentration > 0.25% because lower concentrations of the anesthetic may lead to decreased efficacy. 4,42,43 Given that distribution of the injectate around the optic nerve was only 90° to 180° in 3 of 6 PBA-treated eyes, it is possible that a larger volume (4 mL) was indicated for PBA. Addition of the contrast agent in the present study also may have affected distribution of the bupivacaine, but it was essential for the CT monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Additionally, these techniques provide excellent extraocular muscle akinesia that can replace the use of neuromuscular blocking agents and avoid the need for positive pressure ventilation, both of which are often required for intraocular surgery. 1,[7][8][9][10] As with other regional anesthetic techniques, use of RBA and PBA may reduce the requirements for general anesthetic agents during surgery and thus reduce the adverse effects of these drugs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Placement of a scleral buckle entails extensive dissection of the conjunctiva, Tenon's capsule and sclera, requiring repeated traction on extra-ocular muscles, leading to an increased incidence of the oculocardiac reflex and more postoperative pain [4]. In the study by Shende et al [1] the time to administration of first analgesic rescue medication was similar in the peribulbar and GA groups, which may have been due to the lower concentration of bupivacaine used (0.25%) and the use of long-acting opioid analgesia (morphine) in the GA group.…”
Section: Discussionmentioning
confidence: 99%
“…A high incidence of postoperative pain and postoperative nausea and vomiting (PONV) are attributed to increased intra-ocular pressure due to expansion of the gas bubble or tight buckling or encirclement, particularly when performed under general anaesthesia [1][2][3]. The reluctance to use local anaesthesia alone for vitreoretinal surgery may stem from the longer, more unpredictable and uncomfortable nature of such surgery [4].…”
mentioning
confidence: 99%